Peptide Microarrays Methods and Protocols - Cretich, Marina;Ed. Chiari, Marcella;Ed (Springer protocols (Series); Methods in molecular biology (Clifton, N.J.), v. 570., 2009)
Due to their versatility, along with the diminishing costs of library synthesis and the growth of commercial support, peptide microarrays will likely expand beyond being just a research tool into an adaptable and powerful platform to be harnessed for wider drug discovery and point-of-care applications. In Peptide Microarrays: Methods and Protocols, experts in the field provide a cutting-edge view of peptide array technology, its applications, and technical issues. After examining how peptides can characterize proteins and clarify, at the amino acid level, the molecular recognition events in which they are involved, the volume goes on to cover topics such as the production and use of peptide arrays for enzyme and binding motifs characterization, epitope mapping, and diagnostics, the newest technological advancements, as well as software and web tools for the design of peptide arrays and for the analysis of output data. As a volume in the highly successful Methods in Molecular Biology series, chapters include brief introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and notes on troubleshooting and avoiding known pitfalls. Authoritative and easy-to-use, Peptide Microarrays: Methods and Protocols promises to serve scientists with its unique insights and novel solutions in peptide array technology in order to advance this vital field.